Empowering Early Education: Developing a Hijaiyah Game for Preschoolers - Yulianto, Ade Rizki; Hendri, Ainayah Syifa; Sudaryanto, Aninditawidagda Pandam; Hanif, Muhammad Iqbal (Khazanah Informatika : Jurnal Ilmu Komputer dan Informatika, 2024)
Early education is very important to create a basis for learning and holistic development in preschool children. So we need interesting and interactive learning media to maximize children's learning potential. This research aims to help children achieve learning goals and dig deeper about how to develop interactive hijaiyah games that are creative and in accordance with the characteristics of preschool-aged children so that they can achieve learning goals, where educational games are designed to improve students' ability to think critically and increase their concentration. The system was tested using Black Box and the System Usability Scale (SUS) Testing. The results of system testing show that each button and feature in the educational game application for learning hijaiyah letters runs well and is suitable for preschool-age children with the SUS.